ADOPSI TEKNOLOGI DALAM PERSIAPAN MENGHADAPI RISIKO TEKNIS USAHATANI PADI AKIBAT PERUBAHAN IKLIM - Yamin, Muhammad; Ayundari, L. Defica; Andelia, Siti Ramadani; Tafarini, Meitry Firdha (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
Regional transformative adaptation due to a changing climate needs to be done. Due to low production, climate change has complex effects on rural communities, especially farmers' incomes. Analysis of the level of technical risk of lowland rice farming in swamp land needs to be carried out to assist in implementing actions to deal with climate change. The purpose of this study is to identify and describe the risks faced by farmers, to analyze the technical level and value of risk management in carrying out, to find out how farmers behave in dealing with technical risks of farming, and to adopt technologies such as what rice farmers do due to climate change. This research was conducted in December 2022. The method used was a survey method conducting interviews using a questionnaire with rice farmers in Sudimampir Village. The sampling method uses simple random sampling by taking 90 samples. The results of this study are (1) Farming risks that occur due to climate change are floods, droughts, and pest attacks. (2) The technical risk level of lowland rice farming due to climate change is low, with a coefficient of variation (CV) of 0.04 and a lower limit (L) of 2,610.23. The technical risk management value obtained is 3,169.27 kg/ha/year. (3) The behavior of careful farmers is divided into 3 phases, namely before, during, and after planting in the face of climate change, (4) the opinion of farmers who adopt the six technologies is higher than farmers who apply less than six technologies. Identified adaptation practices include; Tractors, organic fertilizers, inorganic fertilizers, pesticides, superior varieties of seeds, water managers, harvesting machines, and threshing machines.